The egg morphology of some species of Sennius Bridwell (Coleoptera: Chrysomelidae: Bruchinae) based on scanning electron micrographs - Caron, Edilson; Ribeiro-Costa, Cibele S.; Linzmeier, Adelita M. (Zootaxa, 2004)
Eggs of Sennius crudelis Ribeiro-Costa & Reynaud, S. nappi Ribeiro-Costa & Reynaud and S. bondari (Pic) are described based on scanning electron micrographs and compared with eggs of other species of Bruchinae (Chrysomelidae).